m6A-modified lincRNA Dubr is required for neuronal development by stabilizing YTHDF1/3 and facilitating mRNA translation - Huang, Jiansong; Jiang, Bowen; Li, Guo-Wei; Zheng, Dandan; Li, Mingyi; Xie, Xuan; Pan, Yuxiang; Wei, Manyi; Liu, Xiaoyan; Jiang, Xingyu; Zhang, Xu; Yang, Li; et al. (Cell reports (Cambridge), 2022)
Long intergenic noncoding RNAs (lincRNAs) are crucial regulators in numerous biological processes. However, the functions and mechanisms of m6A-modified lincRNAs in neuronal development remain unclear. Here, we report an m6A-modified lincRNA, Dppa2 upstream binding RNA (Dubr), abundantly expressed at the early developmental stage of dorsal root ganglion (DRG) and cerebral cortex. Silencing Dubr impairs axon elongation of DRG neurons and axon projection and migration of cortical neurons, whereas lacking m6A modification of Dubr fully loses its functions. Mechanically, Dubr interacts with m6A-binding proteins, the YTHDF1/3 complex, through its m6A motifs to protect YTHDF1/3 from degradation via the proteasome pathway. Furthermore, Tau and Calmodulin are regulated by YTHDF1/3 and m6A-modified Dubr. Overexpression of YTHDF1/3 not only rescues the reduced Tau and Calmodulin but also restores axon elongation of DRG neurons by Dubr knockdown. This study uncovers a critical role of m6A-modified lincRNA in neuronal development by regulating the degradation of RNA-binding protein.Long intergenic noncoding RNAs (lincRNAs) are crucial regulators in numerous biological processes. However, the functions and mechanisms of m6A-modified lincRNAs in neuronal development remain unclear. Here, we report an m6A-modified lincRNA, Dppa2 upstream binding RNA (Dubr), abundantly expressed at the early developmental stage of dorsal root ganglion (DRG) and cerebral cortex. Silencing Dubr impairs axon elongation of DRG neurons and axon projection and migration of cortical neurons, whereas lacking m6A modification of Dubr fully loses its functions. Mechanically, Dubr interacts with m6A-binding proteins, the YTHDF1/3 complex, through its m6A motifs to protect YTHDF1/3 from degradation via the proteasome pathway. Furthermore, Tau and Calmodulin are regulated by YTHDF1/3 and m6A-modified Dubr. Overexpression of YTHDF1/3 not only rescues the reduced Tau and Calmodulin but also restores axon elongation of DRG neurons by Dubr knockdown. This study uncovers a critical role of m6A-modified lincRNA in neuronal development by regulating the degradation of RNA-binding protein.